The Trap Architecture of Utricularia multifida and Utricularia westonii (subg. Polypompholyx) - Płachno, Bartosz J.; Świątek, Piotr; Adamec, Lubomír; Carvalho, Samanta; Miranda, Vitor F. O. (Frontiers in Plant Science, 2019)
Utricularia are carnivorous plants which have small hollow vesicles as suction traps that work underwater by means of negative underpressure for capturing small animal prey. Utricularia multifida and U. westonii have specific thick-walled traps, which are triangular in a transverse section but their functioning is unclear. Some authors suggest that the trap door in U. multifida acts as a simple valve without a suction trapping mechanism. Our main aim was to check the anatomical trap characters which are responsible for possible water outflow and maintaining negative underpressure as main functional parts of the active trap suction mechanism in both species. Using different microscopic techniques, we investigated the ultrastructure of external trap glands, quadrifids, glands near the entrance (bifids,monofids), and also pavement epithelium. Quadrifids of both species have a similar structure to those known in other species from the genus, which possess the suction trap mechanism. Glands near the entrance in U. multifida and U. westonii, which are responsible for water pumping in other species, are standardly developed and have pedestal cells which are transfer cells. The transfer cells also occur in glands of the pavement epithelium, which is again standardly developed. Simple biophysical tests did not confirm reliably neither the negative underpressure formation in the traps nor the watertightness of the entrance in both species. Our anatomical results indirectly support the hypothesis that both species have suction traps like all other Utricularia species, but the biophysical data rather suggest a passive valve mechanism.